Radiation-induced sarcomas: A single referral cancer center experience and literature review - Laurino, Simona; Omer, Ludmila Carmen; Albano, Francesco; Marino, Graziella; Bianculli, Antonella; Solazzo, Angela Pia; Sgambato, Alessandro; Falco, Geppino; Russi, Sabino; Bochicchio, Anna Maria (Frontiers in Oncology, 2022)
Background and objective The oncogenic effect of ionizing radiation is widely known. Sarcomas developing after radiation therapy (RT), termed “iatrogenic disease of success”, represent a growing problem, since the advancements in cancer management and screening programs have increased the number of long-term cancer survivors. Although many patients have been treated with radiation therapy, only few data are available on radiation-induced sarcomas (RIS). Methods We examined the medical and radiological records of 186 patients with histologically proven soft tissue and bone sarcomas, which referred to IRCCS CROB Centro di Riferimento Oncologico della Basilicata from January 2009 to May 2022. Among them, seven patients received a histological diagnosis of secondary RIS, according to Cahan’s criteria. Clinicopathological features and treatment follow-up data of RIS patients were retrospectively analyzed. Results Among these secondary RIS, five arose in irradiated breast cancer (5/2,570, 0.19%) and two in irradiated head and neck cancer (2/1,986, 0.10%) patients, with a mean onset latency time of 7.3 years. The histology of RIS was one desmoid tumor, two angiosarcomas, one chondrosarcoma, two leiomyosarcomas, and one undifferentiated pleomorphic sarcoma. Out of the seven RIS, one received radiotherapy, one received electrochemotherapy (ECT), one received a second-line chemotherapy, three were subjected to three lines of chemotherapy, and one underwent radiofrequency ablation, chemotherapy, and ECT. Median survival time is 36 months. No significant survival differences were found stratifying patients for age at RT, latency time, and age at RIS diagnosis. Conclusions RIS represents a possible complication for long-survivor cancer patients. Therefore, adherence to a strict follow-up after the radiation treatment is recommended to allow early diagnosis and optimal management of RIS patients. After the planned follow-up period, considering the long-term risk to develop a RIS, a specific multispecialty survivorship care plan could be of benefit for patients.